2012
DOI: 10.1364/ao.51.005060
|View full text |Cite
|
Sign up to set email alerts
|

White-light ellipsometer with geometric phase shifter

Abstract: We describe a simple spectroscopic ellipsometer that uses a geometric phase shifter and a white-light source to generate a small number of phase-stepped intensities I(λ), which are recorded by a spectrometer. The ellipsometric angles ψ and Δ are easily calculated from these intensities at each wavelength simultaneously. We show that errors in Δ due to the nonideal behavior of the achromatic quarter-wave plate in the phase shifter can be made small by suitably adjusting the azimuth of the linearly polarized lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Compared to the spectra taken in Watkins' ellipsometers [3][4], the spectrum taken by RSCE has two harmonic frequency components: …”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the spectra taken in Watkins' ellipsometers [3][4], the spectrum taken by RSCE has two harmonic frequency components: …”
Section: Theorymentioning
confidence: 99%
“…Spectroscopic ellisometry is widely used in semiconductor industry owing to its significant power to characterize thinfilm structures [1][2][3][4]. Rotating compensator is a common modulation method for spectroscopic ellipsometry [1][2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decade ago, it was suggested that additional polarization sensitive [36] or spatial filtering [37] can significantly broaden the spectral performance of Pancharatnam-Berry phase elements. However, the experimental efforts were confined to far-infrared spectral range and did not demonstrate the polarization sensitive beam cleaning as spatial filtering was performed instead [37].…”
Section: Introductionmentioning
confidence: 99%
“…Under the method, rotations are needed for both the polarizer and analyzer. Thus, polarization independent light source and spectrometer are required for the spectral-calibration with Lin's method [7] .…”
mentioning
confidence: 99%